Implementation of individualized educational plan and its challenges in ngala secondary school for the deaf, nakuru county, kenya - and Jebet Nellah, Kipyegon; Bunyasi Awori, Beatrice; Irangi Wamocho, Franciscah (2022)
The study aimed to establish the challenges in the implementation of the individualized educational plan in schools for students with hearing impairment at Ngala Secondary School for the Deaf in Nakuru County, Kenya. Data was collected from a target population of ninety-eight students, thirteen teachers and one administrator through purposive and stratified random sampling techniques. Purposive sampling was used on school administrators and teachers to select all 13 teachers and 1 school administrator. On the other hand, stratified random sampling was used to select a total of 24 students. The study sample comprised 24 students, 13 teachers and 1 administrator leading to a total of 38 respondents. The research instrument included the use of questionnaires, interview schedules and document analysis. A pilot study was conducted at Kedowa Secondary School for the Deaf to enhance the reliability and validity of the research instruments. Quantitative data were cleaned, labelled, coded, entered into a computer and organized using Statistical Package for Social Sciences (SPSS) version 30. Quantitative data were analyzed statistically using descriptive statistics such as percentages and frequencies. The analyzed data were presented using tables, bar-graphs and pie-charts. Qualitative data collected were grouped into different themes, presented as a narrative and discussed based on the objectives of the study. Findings revealed that the major challenge towards implementation IEP was the lack of adequate teaching and learning resources. The study concluded that the major solutions to the challenges facing teachers in developing and implementing IEP suggest that the provision of adequate resources for IEP were anticipated to enhance the academic achievement of students with hearing impairment. The study recommended that the Ministry of Education and other stakeholders should help acquire adequate resources for students with hearing impairment. Article visualizations: